Existence of periodic solutions for nonlinear Lienard systems - Wan Se Kim (International Journal of Mathematics and Mathematical Sciences)
We prove the existence and multiplicity of periodic solutions for nonlinear Lienard System of the type x″(t)+ddt[∇F(x(t))]+g(x(t))+h(t,x(t))=e(t) under various conditions upon the functions g, h and e.